Behavioral activation / inhibition systems and lifestyle as predictors of mental disorders in adolescent athletes during Covid19 pandemic - Morteza Homayounnia Firoozjah; Alireza Homayouni; Shahnaz Shahrbanian; Shaghayegh Shahriari; Diana Janinejad (BMC, 2022)
Abstract Background The following study investigates the correlational relationship between behavioral activation/inhibition systems, lifestyle and mental disorders in Adolescent Athletes during the Covid-19 pandemic. Methods: Research methods are descriptive and correlational; "Of the eligible participants who were available during a COVID-19 quarantine period from June through August 2020 (N = 180), the Krejcie and Morgan Sampling Method was used to simplify the process of determining the sample size for a finite population [46], resulting in a calculation of N = 130 sample participants. to respond to Carver & White's Behavioral activation/inhibition systems Scale (BIS/BAS), Mille's Lifestyle Questionnaire and Goldberg & Williams's General Health Questionnaire (GHQ-12). Data was analyzed using linear regression analysis and Pearson's correlation coefficient. Results: Findings showed a positive correlation of statistical significance between behavioral inhibition systems (BIS) and mental disorders in Adolescent Athletes at the 0.01 level and a negative correlation of statistical significance between scaling components of the behavioral activation systems (BAS), lifestyle and mental disorders in Adolescent Athletes at the 0.05 level. Conclusions: Analyzing the data, it can thus be concluded that whilst behavioral inhibition and activation systems seem to work together to significantly predict mental disorders, lifestyle cannot.